The Left Side of History : World War II and the Unfulfilled Promise of Communism in Eastern Europe - Ghodsee, Kristen Rogheh, 1970- (Book collections on Project MUSE., 2015)
Kristen Ghodsee tells the stories of fighters and activists who worked for Communist ideals in Bulgaria and shows how the dreams of the Communist past hold enduring appeal for those currently disappointed by the promises of democracy.